Expression of Ki67 as detected by MIB-1 and its association with histopathological high-risk factors among patients with retinoblastoma tumour: a cross-sectional study. Issue 1 (12th September 2022) - Vuhahula, Edda AM; Jumanne, Shakilu; Yahaya, James
Abstract : Objectives: This study aims to investigate the expression of Ki67 in formalin-fixed paraffin-embedded tissue blocks from patients with a diagnosis of retinoblastoma tumour (RbT) as well as determining its association with histopathological high-risk factors (HHRFs). Methods and analysis: Retrospectively, a total of 194 eyeball specimens from 163 children with RbT were reviewed at Muhimbili National Hospital between 2009 and 2013. Immunohistochemical expression of Ki67 using MIB-1 antibody (Abcam, batch ab93680, Cambridge, UK) was determined and correlated with the conventional HHRFs. The predictors of Ki67 expression were determined using binary logistic regression model in multivariate analysis. A two-tailed p<0.05 was considered statistically significant. Results: Majority (67.5%) of the patients had leukocoria and extraocular disease was found in 20.9% of all the patients. High expression of Ki67 was present in 63.8% of the 80 eyeballs that were tested. Massive choroidal invasion (adjusted OR (AOR)=9.32, 95% CI=2.82 to 10.89), positive retrolaminar optic nerve invasion (AOR=3.01, 95% CI=4.43 to 9.11), positive surgical margin (AOR=7.10, 95% CI=1.63 to 11.40) and pT4 (AOR=7.49, 95% CI=0.12 to 0.89) were the potential HHRFs that were associated with Ki67 overexpression. Conclusion: Overexpression of Ki67 may be of prognostic value for patients with RbT as it has been shown in the present study that high expression was common in tumours with massive choroidal invasion, positive retrolaminar optic nerve invasion, positive surgical margin and advanced tumour stage, which are the conventional HHRFs associated with prognosis of RbT.